Aspects of the privatization of basic sanitation in Brazil - Borges, Ana Claudia Giannini; Britto, Marcel (Electronic Journal "Fórum Ambiental da Alta Paulista", 2025)
Objective - to outline aspects of the privatization of basic sanitation in Brazil.Methodology - a brief bibliographical and documentary study was carried out to support the analysis of secondary data collected from the National Sanitation Information System (SNIS), the Ministry of Cities, the National Bank for Economic and Social Development (BNDES) and the Central Bank, during varying periods, but with a focus on identifying and describing the presence of the private sector in public basic sanitation services.Originality/relevance - we sought to expand the database to be considered for a more complete analysis of the subject.Results - given that basic sanitation is a fundamental human right and that universalization suggests an unwillingness to shift the public interest to private companies and foreign capital, there is a trend towards both privatization and denationalization.Theoretical/methodological contributions - articulation between the normative references and the different quantitative indicators on basic sanitation, presenting the trend towards privatization of these public services.Social and environmental contributions - presenting the heterogeneous distribution of basic sanitation services which, despite the legal requirement for universalization and quality, reveals the concentration and inequality accentuated by the socially exclusionary and environmentally fragile privatization process.
Keywords: Basic sanitation; Privatization; Denationalization